Protocol: A randomised controlled trial evaluation of Cancer Focus NI's 'Dead Cool' smoking prevention programme in post-primary schools. (2016) - Dunne, L.; Thurston, A.; Gildea, A.; Kee, F.; Lazenbatt, A.
Highlights: This protocol outlines a trial of a smoking prevention programme in Northern Ireland. Year 9 students completed a survey and carbon monoxide testing at three times points. This work explores planned behaviour theory and health outcomes for young people. The findings may have implications for school based smoking prevention programmes. Abstract: This paper presents a research protocol for a randomised controlled efficacy trial of the 'Dead Cool' smoking prevention programme. Dead Cool is a three to four-hour programme designed to be used by teachers with Year 9 students in Northern Ireland. The main outcome of the programme is to prevent students from starting to smoke. The protocol reports a research design intended to test the efficacy of the programme in 20 post-primary school settings. Selected schools included those from secondary /grammar/integrated/single sex/coeducational, rural and urban schools from both the maintained and controlled state sector and independent sector schools. Outcome measures include self-reported behaviours, monitoring of carbon monoxide (CO) in exhaled breath and focus groups designed to assess implementation fidelity and opinions on efficacy in intervention schools and explore the 'counterfactual' potential treatments in control schools.